Variability Studies in Induced, Mutants of Moth Bean on Rainfed Arid Lands - Kumar, D (Annals of Arid Zone, 2016)
In genetically diverse and stabilized mutant lines of moth bean (Vigna aconitifolia (Jacq.) Marechal), irrespective of the year, numher of pods plan-1 had the maximum estimates of GCV (49%), broad sense heritability (69%) and the genetic gain (78-85%).Heritability for the grain yield during dry year was moderate (46%), but was quite high for days to 50% flowering (74.20%).During dry season. plant height and number of pods plant-1 had significant positive association. The days taken to 50% flowering and the number of pods plant-1 were most important traits for yield improvement through selection. during dry and the wet seasons. respectively.